2019
DOI: 10.5812/aapm.78905
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Cognitive-Behavioral Training on Pain Self-Efficacy, Self-Discovery, and Perception in Patients with Chronic Low-Back Pain: A Quasi-Experimental Study

Abstract: Background Correcting false cognitions and establishing preventive behaviors in patients with chronic low-back pain can improve self-efficacy and self-discovery of these patients against the physical and psychological consequences of chronic back pain through reinforcing thoughts and constructive behaviors. Objectives This study aimed to investigate the effectiveness of cognitive-behavioral training in self-efficacy, self-discovery, and pain perception of patients with … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
14
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 12 publications
(15 citation statements)
references
References 32 publications
1
14
0
Order By: Relevance
“…32,33 In these persistent pain populations, promising results have been achieved with cognitive behavioural training on pain perception and quality of life. 34 However, in the studies included in our review, no such finding was found except in one study, 23 where the presence of agitation after ICU stay was a risk factor for persistent pain. In trauma populations, the fear of movement and pain catastrophising accounted for more overall variance in pain intensity and interference than depressive symptoms.…”
Section: Addressed Thementioning
confidence: 70%
“…32,33 In these persistent pain populations, promising results have been achieved with cognitive behavioural training on pain perception and quality of life. 34 However, in the studies included in our review, no such finding was found except in one study, 23 where the presence of agitation after ICU stay was a risk factor for persistent pain. In trauma populations, the fear of movement and pain catastrophising accounted for more overall variance in pain intensity and interference than depressive symptoms.…”
Section: Addressed Thementioning
confidence: 70%
“…People with LBP express a strong desire for precise, consistent, personalised information on prognosis, treatment options, and self-management strategies related to healthcare and occupational issues [ 14 ]. Perceived fear-avoidance beliefs, catastrophic thinking, and perceived disability make the symptoms more severe than they are [ 15 , 16 ]. Cognitive-behavioural education may be used to increase physical performance, reduce pain level, and even decrease depression in people with LBP [ 17 ].…”
Section: Introductionmentioning
confidence: 99%
“…Feedback to trainees is one of the main areas that should be focused on DOPS (8,28,29). Our results demonstrated that Re-DOPS decreased the time needed for feedback to the residents, which could be considered an advan- Based on the latter classification, the results of our study could exactly cover 3 of 4 areas from the above list (7, 8, 10, 30), including: Context (i.e., time to feedback to anesthesiology residents); Users (i.e., trainees' satisfaction); Outcome (i.e., the time needed for the 1st DOPS compared with the 2nd DOPS).…”
Section: Discussionmentioning
confidence: 99%